2021
DOI: 10.31234/osf.io/fgkwq
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Creative people use memory differently: Divergent thinking modulates how episodic memory is combined with semantic knowledge

Abstract: The ability to generate novel ideas, known as divergent thinking, is dependent on both semantic knowledge and episodic memory. Semantic knowledge and episodic memory are known to interact to support memory decisions, but it is not known how they may interact to support divergent thinking. We addressed this question by examining whether divergent thinking ability moderates interactions between semantic knowledge and different episodic memory processes in a spatial memory task. Participants completed the Alterna… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The fact that the analogous processes underlying change detection (i.e., perceiving, sensing, and unconscious change detection) were also able to be isolated in this way, such that they dissociated along the lines of eye movement behavior, highlights the versatility of this trial-level confidence-based scale. Other studies using this method have found that memory processes isolated in this way also (1) relate to different patterns of eye movements -including dispersion and resampling -during search, encoding, and retrieval (Ramey et al, 2019;Ramey, Henderson, et al, 2020a), (2) show differential interactions with schema knowledge (Ramey et al, 2022;Ramey, Yonelinas, et al, 2020b), and (3) predict real-world outcomes such as creative ability (Ramey & Zabelina, 2021). Thus, the present findings add to a growing body of work showing that this recently developed method can be fruitfully applied to isolate dissociable cognitive processes in a variety of settings.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the analogous processes underlying change detection (i.e., perceiving, sensing, and unconscious change detection) were also able to be isolated in this way, such that they dissociated along the lines of eye movement behavior, highlights the versatility of this trial-level confidence-based scale. Other studies using this method have found that memory processes isolated in this way also (1) relate to different patterns of eye movements -including dispersion and resampling -during search, encoding, and retrieval (Ramey et al, 2019;Ramey, Henderson, et al, 2020a), (2) show differential interactions with schema knowledge (Ramey et al, 2022;Ramey, Yonelinas, et al, 2020b), and (3) predict real-world outcomes such as creative ability (Ramey & Zabelina, 2021). Thus, the present findings add to a growing body of work showing that this recently developed method can be fruitfully applied to isolate dissociable cognitive processes in a variety of settings.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, information at the two extremities of the U-shape activates different brain regions at encoding (van Kesteren, Ruiter, Fernández, & Henson, 2012): While processing information, the medial prefrontal cortex either triggers rapid learning of schema-congruent information into the neocortex or activates the hippocampus in the medial temporal lobe to encode schema-incongruent events. However, differences in memories are also suspected at retrieval as remembering incongruent events engages the network for source memory (Brod, Lindenberger, Werkle-Bergner, & Shing, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, distinct novelty, a good candidate for creativity as its high incongruence naturally provides novel original associations, is thought to induce episodic memories. Although most of the research on creativity has focused on semantic memory, researchers have recently demonstrated the role of episodic memory in creative processes as well as its interaction with semantic memory during divergent thinking (Ramey & Zabelina, 2021).…”
Section: Introductionmentioning
confidence: 99%